Cross-sector partnership as a determinant of development - the perspective of public management = Partnerstwo międzysektorowe jako determinanta rozwoju - perspektywa zarządzania publicznego - Wyrwa, Joanna (Zielona Góra: Faculty of Economics and Management Press)
Challenges faced by organizations in the area of public management today force them to seek new organizational forms to build a competitive advantage. In contemporary public management, two trends in particular can be observed. The first is to depart from repeatability and duplication of actions, and to follow instructions with a view to focusing on creativity and efficiency in solving problems.
Keywords: partnerstwo; współpraca międzysektorowa; partnerstwo publiczno-społeczne; partnership; cross-sector cooperation; public-social partnership